COMPLEX РREVENTION OF DESTRUCTIVE MENTAL STATES OF THE HEADS OF SOCIAL AND PSYCHOLOGICAL SERVICE DEPARTMENTS OF PENAL INSTITUTIONS - Чичуга, М. М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
The article highlights the comprehensive prevention of destructive mental states of the heads of social and psychological service departments of penal institutions. The main directions of destructive mental states and properties of the heads of social and psychological services are human resources of management, organizational and psychological management. In the article the features of the implementation of personnel and organizational management directions and recommendations for the heads of departments of social and psychological services are examined. Also the structure of psychological direction and the recommendations for staff of penal institutions for its implementation by the heads of departments of social and psychological services is elaborated. The structure of psychological direction includes: psychological support for young workers in the context of their social and psychological adaptation to professional activity and psychological assistance in emergencies of their performance